Perkembangan Islam di Asia Tenggara: Kajian Historis di Brunei Darussalam, Filipina, dan Thailand - Isramijz Bayau; Ansar Tohe (Al-Kindi, 2026)
This study aims to analyze the historical development of Islam in Southeast Asia, focusing on Brunei Darussalam, the Philippines, and Thailand, and to identify the factors influencing the different patterns of Islamic development in these countries. The research employed a qualitative approach using library research combined with the historical method. Data were collected from books, scientific journals, historical documents, and other relevant academic sources, and were analyzed through descriptive, historical, and comparative approaches. The findings reveal that Islam spread across Southeast Asia primarily through peaceful penetration, including trade, da'wah, intermarriage, education, and diplomatic relations. The study also indicates that the Arab, Gujarat, and Persian theories complement one another in explaining the Islamization process. Furthermore, Brunei Darussalam demonstrates a distinctive model of Islamic development, where Islam functions not only as the religion of the majority but also as the ideological foundation of the state through the Melayu Islam Beraja (MIB) philosophy. The study concludes that the development of Islam in Southeast Asia has been shaped by historical, political, social, and cultural factors, resulting in diverse patterns of Islamic growth in each country.